Anna Bruce: capstone - Bruce, Anna, artist (Colorado State University. Libraries, 2025)
The artist's statement: Objects speaking through the ancestors, giving voice to future possibilities. Family traditions are the foundation of my work—everything I make begins with how humans root themselves in place through what we grow, eat, and create—how we bring the land indoors and shape it into items that make a "home." I search for forms that could hold both utility and symbolism—patterns that echo family, mark time, and swirl with the sense of eons. Centuries of shared knowledge, passed down through ancestors, leading to where I now create. Speaking to me as I place my hands in clay, as I light a torch flame. Objects of functionality, objects of beauty, objects of objectification. These pieces live between functionality and beauty, between the intimate and the symbolic. Objects offering pathways to future possibilities. They speak to how I have touched them, changed and molded them, and how my life, choices, and memories have shaped their final form: esthetics and functionality dancing together, looking for originality but finding deep conversations among souls. A little bit witchy, with a dash of feminine mysteries, remembrances of childhood with a twist of elevation, tinged with reminders of colonization. Shared knowledge guides my hands, ancestors and spirits speaking in the language of artists long gone. My work is an intersection of what has been inherited and what I am still learning. Through these objects, I honor where I come from and carve space for where I am going.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metals; pottery